Effect of Type of Organic Fertilizer and Dosage of Kno3 on The Growth and Results Of Shallot Plant (Allium ascalonicum L.) - Made Kresna Bayu; Made Sri Yuliartini; Luh Kartini (Warmadewa University Press, 2023)
This study aims to determine the effect of the type of organic fertilizer and the dose of KNO3 on the growth and yield of shallot plants. This research was conducted from March to May 2023, which took place in Subak Sampalan Dlod Margi, Jalan Raya Kusamba, Dawan District, Klungkung Regency with an altitude of 15 meters above sea level. The design used in this study was a randomized block design (RBD) with 2 factors arranged factorially. The first factor was using 3 types of organic fertilizers as much as 20 tons ha of each type, namely P1: 20 tons/ha of rabbit manure, P2: 20 tons/ha of kerambitan agro organic fertilizer, P3: 20 tons/ha of lemeksari compost and the second factor was using KNO3 which consisted of 3 levels, namely K1: 50 kg/ha, K2: 100 kg/ha and K3: 150 kg/ha thus obtaining 9 combinations of treatments which were repeated 3 times. The interaction between the type of organic fertilizer with the dose of KNO3 (P×K) and the type of organic fertilizer (P) had no significant effect (P≥0.05) on all observed variables. KNO3 (K) dose treatment had a significant effect (P<0.05) on tuber fresh weight per clump, tuber oven dry weight per clump and harvest index; no significant effect (P≥0.05) on other variables. KNO3 dose of 100 kg/ha (K2) gave the highest tuber fresh weight and oven dry weight per clump, namely 65.16 g and 6.38 g; which increased by 77.64% and 90.44% when compared to the lowest fresh weight and oven dry weight of tubers per clump obtained at the KNO3 dose of 50 kg/ha (K1), namely 36.86 g and 3.35 g.